Implementation of the 7P marketing mix strategy in enhancing the attractiveness of MI Al Husna Tangerang - Tri Joko Susanto; Fauzi Muharom; Toto Suharto (ARKA INSTITUTE, 2026)
This study examines the implementation of the 7P marketing mix (Product, Price, Place, Promotion, People, Process, and Physical Evidence) in enhancing the attractiveness of Madrasah Ibtidaiyyah Al Husna, Tangerang. Using a qualitative case study approach, data were collected through in-depth interviews, observations, and document analysis involving 10 purposively selected informants, comprising the principal, vice principal for curriculum, four teachers, two administrative staff members, and two parents. Data were analyzed using the interactive model of Miles and Huberman through data reduction, data display, and conclusion drawing, supported by thematic coding based on the 7P framework. The findings indicate that the integrated implementation of the 7P marketing mix enhances institutional attractiveness and public trust. The People and Product dimensions are the strongest components, as teacher professionalism and moral integrity build parental trust, while the integration of a Qur’an-based character curriculum with the national curriculum provides distinctive value. Ethical pricing, da’wah-oriented promotion, and inclusive service processes further strengthen accessibility and sustain student enrolment. This study proposes an Integrated Islamic Educational Marketing Model that reframes the marketing mix as a value-based strategy grounded in Islamic ethics, emphasizing value differentiation, ethical service, and trust-based relationships to strengthen institutional competitiveness.